Cerebral strokes with coronavirus infection - Yo'lchiev Elmurod O'ktamjon o'g'li (Genius Journals, 2023)
The main mechanisms of penetration of a new coronavirus infection into the central nervous system, risk factors for the development and forms of cerebral vascular complications, are considered, and their own clinical observation is described. Key words: coronavirus disease, vascular risk factors, neurological complications, strokes.
Keywords: Covid -19; neurological complications; acute cerebrovascular accidents; ischemic stroke